Islamic Financial Literacy Amongst Muslims and Loyalty to Fatwas - Rofiah, Khusniati; Bashori, Yudhi Achmad; Wahid, Soleh Hasan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine the extent of the financial literacy of the Muslim community in Ponorogo and their loyalty to the bank interest fatwa. This paper uses a field research approach using data collection methods in the form of interviews and observations and the analysis techniques used are descriptive-inductive. Based on the analysis of the data obtained, the following conclusions were found: 1. The perception of Ponorogo Muslims is divided into no types, namely agreeing with bank interest fatwas, doubting the existence of bank interest fatwas, and ignoring the provisions of bank interest fatwas. 2. The factors influencing the observance of Ponorogo Muslims are classified into 2 categories, namely those who obey which are divided into observance based on religious values (obedience) and obedience based on religious-rational considerations (internalization observance). Then those who disobey are caused because their legal awareness is still very weak, the causative factor is the nature of the fatwa itself and some of the following: (a) There is still difficult access to Islamic banking in their area; (b) Islamic bank services that tend to be the same as conventional banks; (c) Conventional banks and Islamic banks are practically considered to be no different, both of which have not adhered to sharia principles; 3. By behavioral finance analysis, it is found that (a) Those who agree with fatwas based on religious-rational values are not found any element of bias in them. (b) who doubts that there is an element of bias in the form of overconfidence with the initial information so as not to follow the development of the next information (bias anchoring). And those who ignore fatwas have no element of bias in them because they are supported by the fact that bank interest fatwas have no significant effect on the provisions of fatwas.